Implementasi Model Pembelajaran TGFU ( Teaching Games For Understanding) Dalam Meningkatkan Minat Siswa Terhadap Pendidikan Jasmani - Glauca, Chesia; Topo Yono; Ahmad Sulaiman (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
Interest has a very big influence on learning outcomes, if the learning material being studied does not match the student's learning interests, then the student will not learn as well as possible, because there is no special attraction. So that students are lazy to learn, students do not get satisfaction from the lesson. Interest is a constant tendency to pay attention and remember some activities that someone is interested in, paid attention to continuously accompanied by a sense of pleasure. Students who have high interest encourage students to be more enthusiastic and diligent in their learning, students will always be enthusiastic and always interested in every material taught. A teacher really needs to do various ways to be able to increase student interest in learning. In order for student interest in learning to increase, teachers need to innovate in learning. One thing that teachers need to pay attention to in order to be able to increase interest in learning in physical education. An important play model is owned by teachers in every learning. Good technical group games are not enough to show performance when learning. The purpose of this study was to determine the implementation of technology games for understanding for students in physical education. The research method used was an experiment with a pretest and posttest group design. The population of this study was junior high school students in grade VIII. The sampling technique used in this study was cluster random sampling, with 48 participants. This study was conducted for 6 weeks with 12 meetings with 90 minutes each meeting. Data analysis used paired samples t-test. The results of the study showed that there was a significant influence of the implementation of the Teaching Games for Understanding (TGFU) model. The TGFU model in practice in the field prioritizes a play approach that can encourage students to do various play groups better. The conclusion of this study is that the TGFU model is very effective to be applied in physical education learning groups in high school. In further research, the TGFU model can be applied to different levels of education.